2022
DOI: 10.1186/s12884-022-05078-z
|View full text |Cite
|
Sign up to set email alerts
|

Iranian women’s perception on the determinants of birth experience: a qualitative study

Abstract: Background The prevalence of cesarean birth in Iran is very high. Having a negative childbirth experience is one of the reasons that primiparous women provide to prefer caesarean birth over a vaginal birth. This study is aimed to understand women’s perspective on what determines a positive or negative birth experience for them. Methods This qualitative study is a part a mixed method study that was conducted among primiparous women with a previous v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
1
0
2
Order By: Relevance
“…Previous studies have found that women’s understanding of their challenges, predictability and preparation of their situation, and ability to anticipate events concerning pregnancy and childbirth could help them manage pain and alleviate fear and distress during the perinatal period [ 6 8 ]. In addition, the ability to cope with adverse pregnancy events by mobilising appropriate resources could contribute to well mental health [ 9 11 ]. Moreover, a sense of meaning and purpose of childbearing may provide the motivational basis for the couples’ commitment and devotion to the parental transition [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that women’s understanding of their challenges, predictability and preparation of their situation, and ability to anticipate events concerning pregnancy and childbirth could help them manage pain and alleviate fear and distress during the perinatal period [ 6 8 ]. In addition, the ability to cope with adverse pregnancy events by mobilising appropriate resources could contribute to well mental health [ 9 11 ]. Moreover, a sense of meaning and purpose of childbearing may provide the motivational basis for the couples’ commitment and devotion to the parental transition [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Artan sezaryen oranlarının azaltılmasında, kadınların sezaryen doğumu tercihlerinde etkili olan faktörlerin bilinmesinin önemi vurgulanmaktadır (10). Çalışmalarda kadınların sezaryen doğumu tercih etme nedenleri arasında olumsuz doğum algısının ve doğum korkularının önemli bir rol oynadığı belirtilmektedir (4,11).…”
Section: Introductionunclassified
“…Aynı zamanda, çalışma hayatlarındaki mesleki performansları, iş doyumları ve kendi doğum tercihleri de etkilenebilmektedir (17). Bu nedenle ebelerin nitelikli ve kaliteli bakım sunabilmesi için sahip oldukları doğum algısını tanımlamaları ve farkına varmaları gerekmektedir (11). Doğum algısı ile ilgili literatür incelendiğinde; çalışmaların genel olarak gebe\lohusa kadınlar ve eşlerine yönelik olduğu belirlenmiştir (12,18,19).…”
Section: Introductionunclassified